2012
DOI: 10.25011/cim.v35i4.17148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term low-level solvent exposure on cognitive function

Abstract: TurkeyE ects of long-term low-level solvent exposure on cognitive function Abstract Purpose: e e ects of long-term low-level exposures to solvents on cognitive function were investigated.Methods: A total of 389 workers at a gun factory, those exposed to solvents (n=193) and those that were not exposed to solvents during work (n=196), were included. All the workers were given a questionnaire. Cognitive function was evaluated by Mini-mental Status Examination (MMSE) and psychological status was assessed by Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
1
7
0
3
Order By: Relevance
“…Exposed men compared to the non-exposed men presented a signifi cantly lower performance in the TMT-A, ROCF-Copy and ROCF-Recall tests, except for the TMT-B (Tables 1 and 2). This result was expected, since similar fi ndings were found by other studies carried out with men (Saygun et al, 2012;Song et al, 2015;Thetkathuek et al, 2015).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Exposed men compared to the non-exposed men presented a signifi cantly lower performance in the TMT-A, ROCF-Copy and ROCF-Recall tests, except for the TMT-B (Tables 1 and 2). This result was expected, since similar fi ndings were found by other studies carried out with men (Saygun et al, 2012;Song et al, 2015;Thetkathuek et al, 2015).…”
supporting
confidence: 91%
“…In recent years, the number of women hired as gas station attendants has increased in most developing countries and in other industrial activities in Western European countries (Ernstgård, Gullstrand, Löf, & Johanson, 2002). However, most research has been carried out with men (Saygun et al, 2012;Song, Yu, & Lao, 2015;Thetkathuek, Jaidee, Saowakhontha, & Ekburanawat, 2015) or male animals (Beasley, Evansky, & Bushnell, 2012;Zhong et al, 2013), probably because males are still the majority in this type of activity (Vahter et al, 2007), or due to the historical belief that jobs in hazardous environments, including those involving solvents, are restricted to men (Mergler, 2012). These results are eventually generalized to women (Ernstgård et al, 2002) who are exposed to the same tolerance limits based on studies carried out with males (Kawai, Takeuchi, & Ikeda, 2015).…”
Section: Relación Entre Desempeño Neurocognitivo Y Composición Corpormentioning
confidence: 99%
See 1 more Smart Citation
“…The current study, however, found several associations between more specific solvent use measures and depressive symptoms among members of an all-farming sample. Although some studies in other industries have found null effects (Satoh et al 1996; Saygun et al 2012), there is evidence supporting associations between solvent exposure and impaired mental health as measured by a variety of scales (Bowler et al 2001; Escalona et al 1995; Nordling Nilson et al 2010). …”
Section: Discussionmentioning
confidence: 98%
“…However, these studies of neurological effects, particularly of mood and depressive symptoms, among non-agricultural populations have shown inconsistent results (Bowler et al 2001; Escalona et al 1995; Nordling Nilson et al 2010; Satoh et al 1996; Saygun et al 2012). …”
Section: Introductionmentioning
confidence: 99%